ANALISIS KEMUDAHAN PENGGUNAAN DAN KEAMANAN BERTRANSAKSI DALAM MINAT MENGGUNAKAN MOBILE BANKING BANK SYARIAH INDONESIA - Damayanti, Marla; Komariah, Kokom; Sunarya, Erry (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The internet is a set of large computer networks connected to each other globally and the breadth of network coverage such as being able to read and decipher various communication protocols globally, the internet is used to facilitate access to information, facilitate communication, and facilitate other activities and work. One of the business sectors that utilizes internet media in carrying out all their business activities and activities, namely the banking sector. One of the companies in the banking world that innovates and utilizes using internet media is Bank Syariah Indonesia.The purpose of this study was to determine the description of ease of use, transaction security, and customer interest in using Bank Syariah Indonesia Mobile Banking. Knowing the effect of ease of use on customer interest in using Bank Syariah Indonesia Mobile Banking and to determine the effect of transaction security on customer interest in using Bank Syariah Indonesia Mobile Banking. The method used in this research is associative descriptive with sampling using Cluster Sampling. The questionnaire was distributed to Bank Syariah Indonesia customers in Sukabumi City. The data analysis technique used Multiple Regression Analysis assisted by SPSS as a data processing tool.The results of the study showed that perceived convenience has a significant effect on interest in using BSI mobile banking in Sukabumi City. This is evidenced by the value of tcount> ttable = 6.496> 1.652. Perceived security has a significant influence on interest in using BSI mobile banking in Sukabumi City. This is also evidenced by the value of tcount> ttable = 5.560> 1.652.